Dari Pengabdian Ke Profesionalisme: Persepsi Alumni SM3T tentang kualitas Guru dan Revitalisasi Program Daerah 3T - Faizah M. Nur; Fatma Zuhra (Jurnal Educatio FKIP UNMA, 2026)
The Bachelor's Degree Holders Teaching in Frontier, Outermost, and Disadvantaged Regions program – hereinafter referred to as the SM3T program – stands as one of the most strategic affirmative policies in the history of professional teacher preparation in Indonesia. However, the program was discontinued in 2018 without a comprehensive alumni evaluation. This study aims to explore SM3T alumni perceptions of the program's impact on teacher quality, levels of satisfaction, and policy recommendations for revitalization. Employing a mixed-methods explanatory sequential design with 151 alumni, the study found that 94% of respondents had a positive impression, with 34.4% stating that SM3T was an experience that directly impacted their teaching quality. The three main alumni recommendations were increased incentives (31.1%), extended assignment duration (15.2%), and clarity of post-SM3T career pathways (12.6%). A total of 96.7% of respondents supported program revitalization. These findings provide a strong empirical basis for revitalization policies of teacher preparation programs in 3T regions within the framework of the Merdeka Curriculum.